Relación de la inteligencia emocional y desempeño laboral en trabajadores del sector público y privado: revisión aplicada - Arias Guerra, Claudio Andre (2023)
Emotional intelligence is the set of skills that allow a person to develop assertively in different contexts, such as in the work context. Its study has been addressed over time in various parts of the world. For this reason, the present study sought to determine the relationship between emotional intelligence and job performance in workers in the public and private sectors. A systematic search was carried out taking into account the methodological recommendations provided by the PRISMA guide. The databases consulted were Scopus, Web of Science and Scielo. Ten articles that met all the criteria established above were analyzed. The level of study used in these investigations was correlational. As a result, it was found that most of the investigations show results that positively relate EI and job performance in workers in both the public and private sectors. However, due to the little scientific evidence where both study concepts are related, it is difficult to draw solid conclusions about the results obtained. In the future, research should focus on the design of intervention programs on emotional intelligence and evaluate their impact on the work performance of workers.